An accurate Dual Tone Multiple Frequency Detector Based on the Low-Complexity Goertzel Algorithm. - Andritsopoulos, Fotis E. (2009)
This article presents a low complexity dual tone multiple frequency (DTMF) signal detectort hat meets they ternation a Telecommunication Union (ITU) Q.24 DTMF standard while implemented on a general purpose Digital Signal Processor(DSP). The proposed DTMF detectoris based on the Goertzel algorithms and is well suited for a multichannel implementation. Our solution offers increased accuracy and noise margins, while preserving the inherited advantages of the Goertzel algorithm (less memory requirements and computational complexity).